Affective solidarity: Feminist reflexivity and political transformation - Hemmings, Clare (Feminist Theory, 2012)
This article seeks to intervene in what I perceive to be a problematic opposition in feminist theory between ontological and epistemological accounts of existence and politics, by proposing an approach that weaves together Elspeth Probyn’s conceptualisation of ‘feminist reflexivity’ with a re-reading of feminist standpoint through affect. In so doing, I develop the concept of affective solidarity as necessary for sustainable feminist politics of transformation. This approach is proposed as a way of moving away from rooting feminist transformation in the politics of identity and towards modes of engagement that start from the affective dissonance experience can produce. Moving beyond empathy as a privileged way of connecting with others, I argue that the difference between ‘womanhood’ and ‘feminism’ is critical for a universal yet nonessential understanding of what motivates gendered change.
Keywords: approches et analyses; discipline; méthodologie; point de vue situé; rapports sociaux de sexe; ressource en ligne; sciences humaines; solidarité; théories féministes; émotions; épistémologie